Intramolecular Singlet Fission in Individual Graphene Nanoribbons─Competition with a Charge Transfer - Greißel, Phillip; Beneventi, Giovanni Mariano; Weiß, René; Wollny, Anna-Sophie; Dubey, Rajeev K.; Melle-Franco, Manuel; Clark, Timothy; Mateo-Alonso, Aurelio; Guldi, Dirk Michael (Journal of the American Chemical Society, 2025)
Graphene nanoribbons (NRs) constitute a versatile platform for developing novel materials, where their structure governs their optical, electronic, and magnetic properties while also shaping their excited-state dynamics. Here, we investigate a set of three twisted N-doped molecular NRs of increasing length, obtained by linearly fusing perylene diimide to pyrene and pyrazino- or thiadiazolo-quinoxaline residues. By employing various temperature-dependent time-resolved spectroscopy techniques, we reveal how the flexible twisted NR geometry promotes the formation of a mixed electronic state with varying contributions from locally excited and charge-transfer (CT) states. The fate of this mixed state is highly sensitive to the molecular geometry, length, and solvent polarity. For the shortest NR, intersystem crossing dominates the deactivation pathway, efficiently generating triplets in low-polarity solvents. In contrast, for the extended NRs, intramolecular singlet fission (SF) takes place within a single nanoribbon. This is enabled by enhanced superexchange coupling due to a pronounced push-pull nature and the existence of multiple localized π-electron states caused by heteroatom doping, thereby circumventing the need for dimeric interactions typically associated with conventional SF systems. In higher-polarity environments, evidence of a (diabatic) CT state emerges. These findings underscore the intricate relationship between geometry, energy levels, and excited-state dynamics in twisted N-doped NRs.
CRIS-Team Scopus Importer:2025-04-01